Development of Sparkol Videoscribe-Based Learning Media in Fourth-Grade of Elementary School Science Lessons - Salim, Faisal; Usman, Herlina; Aviarizki, Hasna Wulan; Robbyzess, Debima Jejen Junior (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Learning media that are generally used are less attractive and cannot be used optimally independently. Meanwhile, at the fourth-grade level of elementary school, students need engaging media that can be used independently at home. Sparkol Videoscribe-based learning media can help students understand the material and foster interest in learning and independent learning. This study aims to develop Sparkol Videoscribe-based learning media in science lessons for fourth-grade of elementary schools and determine its feasibility. The research method used is Research and Development (RD) which was conducted in two elementary schools in Jakarta. The research model used is 4D with define, design, develop, and disseminate stages. The data collection technique used was a questionnaire. The results related to media expert validation were 86.1%, material expert validation results were 88.8%, and linguist validation results were 94.7%, so overall, it became 89.7% with a very decent category. The results of user trials conducted by teachers and students obtained a value of 92.5% for teacher trials and 92.3% for students. These results make Sparkol Videoscribe-based learning media in the fourth grade of elementary school science lessons feasible. If implemented, it will increase learning effectiveness and motivate learners to be more active and creative.